SOSIALISASI PENGELOLAAN ARSIP MELALUI SISTEM TATA NASKAH TERINTEGRASI DI DIREKTORAT SARANA DAN PRASARANA - Kaylasalma , Nazla; Hartati, Leni (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2025)
Effective and efficient archival document management is a crucial factor in supporting the smooth administration of the Directorate of Facilities and Infrastructure (Dirsarpras). This study aims to analyze the archival document system implemented at Dirsarpras and assess its effectiveness in supporting workflow and decision-making processes. The research employs a qualitative method with a descriptive approach, collecting data through observations, interviews, and document analysis. The findings indicate that the archival document system at Dirsarpras is well-organized through the implementation of a digital system that enables faster and more accurate document storage, classification, and retrieval. Additionally, the monitoring application facilitates document management and activity evaluation, enhancing transparency and accountability in administration. The system also includes a document completeness verification feature to ensure that each archive is systematically documented and meets administrative standards. Therefore, it can be concluded that the archival document system at Dirsarpras functions effectively and contributes to improving the organization’s efficiency and administrative effectiveness.